2020
DOI: 10.1017/ice.2020.328
|View full text |Cite
|
Sign up to set email alerts
|

A survey of infection control strategies for carbapenem-resistant Enterobacteriaceae in Department of Veterans’ Affairs facilities

Abstract: A survey of Veterans’ Affairs Medical Centers on control of carbapenem-resistant Enterobacteriaceae (CRE) and carbapenem-producing CRE (CP-CRE) demonstrated that most facilities use VA guidelines but few screen for CRE/CP-CRE colonization regularly or regularly communicate CRE/CP-CRE status at patient transfer. Most respondents were knowledgeable about CRE guidelines but cited lack of adequate resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…VA guidelines required laboratories to use CLSI M100-S21 or higher, however antibiotic susceptibility testing was performed by each VA laboratory according to their protocol, which may not have been consistent across sites. An electronic survey of 161 Multidrug-resistant Organism (MDRO) Prevention Coordinators at 134 VA Medical Centers (VAMCs) between February 21 and April 30, 2018 found 20.9% of coordinators reported active screening for Carbapenem-resistant Enterobacterales (CRE) and carbapenemase-producing-CRE colonization at their site [ 16 ]. However, each VA may have variability in surveillance and reporting for CRE [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…VA guidelines required laboratories to use CLSI M100-S21 or higher, however antibiotic susceptibility testing was performed by each VA laboratory according to their protocol, which may not have been consistent across sites. An electronic survey of 161 Multidrug-resistant Organism (MDRO) Prevention Coordinators at 134 VA Medical Centers (VAMCs) between February 21 and April 30, 2018 found 20.9% of coordinators reported active screening for Carbapenem-resistant Enterobacterales (CRE) and carbapenemase-producing-CRE colonization at their site [ 16 ]. However, each VA may have variability in surveillance and reporting for CRE [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…An electronic survey of 161 Multidrug-resistant Organism (MDRO) Prevention Coordinators at 134 VA Medical Centers (VAMCs) between February 21 and April 30, 2018 found 20.9% of coordinators reported active screening for Carbapenem-resistant Enterobacterales (CRE) and carbapenemase-producing-CRE colonization at their site [ 16 ]. However, each VA may have variability in surveillance and reporting for CRE [ 16 ]. Only cultures identified as CRAB or CRPA were included in the analysis, and only the last culture per patient was included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey done in 2018, it was found that communication between facilities about Veterans who were colonized or infected with CP-CRE occurred only 38%-42% of the time when the individual was transferred from another VA facility. 10 Often, infection control interventions designed to prevent spread of MDROs are independently implemented by individual health care facilities without clear coordination with other facilities within a healthcare system that may care for the same patients. Efforts limited to a single facility do not account for the potential of inter-facility spread through movement of patients who are colonized or infected with these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…12 And in another VA survey, 70% of facilities did not screen admissions for CP-CRE because they did not think they had a problem with these organisms. 10 Third and finally, because user may select from various email alert options, a potentially engaged user may not receive an alert for months in the event no patients are admitted locally with a qualifying history of the target pathogen (eg C. auris or CP-CRE), such that the optimal number of national weekly users is not yet well established.…”
Section: Discussionmentioning
confidence: 99%